2015
DOI: 10.12659/msmbr.895555
|View full text |Cite
|
Sign up to set email alerts
|

C57BL/6N Mice Are More Resistant to Ehrlich Ascites Tumors Than C57BL/6J Mice: The Role of Macrophage Nitric Oxide

Abstract: BackgroundEffectiveness of the immune defense formed by the genotype often determines the predisposition to cancer. Nitric oxide (NO) produced by macrophages is an important element in this defense.Material/MethodsWe hypothesized that genetic characteristics of NO generation systems can predetermine the vulnerability to tumor development. The study was conducted on mice of 2 genetic substrains – C57BL/6J and C57BL/6N – with Ehrlich ascites carcinoma (EAC). NO production in the tumor was changed using ITU, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…From a physiological perspective, although NO and H 2 S have some similar functions, such as blood vessel relaxation, they act on different downstream targets, including respectively soluble guanylyl cyclase/cyclic guanosine monophosphate (sGC-cGMP) and the potassium (K + ) channel (Mustafa et al, 2009). In peripheral macrophages, the expression of CD206, a M2 marker, is insensitive to the change of endogenous NO content, whereas elevation of H 2 S production by CBS overexpression not only inhibits M1 markers but also promotes M2 markers (Chao et al, 2015; Kalish et al, 2015). These observations provide the possible differences between NO and H 2 S in the regulation of microglial polarization.…”
Section: Discussionmentioning
confidence: 99%
“…From a physiological perspective, although NO and H 2 S have some similar functions, such as blood vessel relaxation, they act on different downstream targets, including respectively soluble guanylyl cyclase/cyclic guanosine monophosphate (sGC-cGMP) and the potassium (K + ) channel (Mustafa et al, 2009). In peripheral macrophages, the expression of CD206, a M2 marker, is insensitive to the change of endogenous NO content, whereas elevation of H 2 S production by CBS overexpression not only inhibits M1 markers but also promotes M2 markers (Chao et al, 2015; Kalish et al, 2015). These observations provide the possible differences between NO and H 2 S in the regulation of microglial polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported an increased proinflammatory response in B6N mice compared to that in B6J mice 10,20 . Macrophages from B6N mice displayed a more activated M1 phenotype and produced more NO than those from B6J mice in a tumor model 19 . Obesity is often described as a chronic state of low-grade inflammation 16,17,48 .…”
Section: Discussionmentioning
confidence: 92%
“…Immunological differences between B6 substrains have been described previously. B6N mice exhibited a more activated and proinflammatory phenotype than B6J mice 10,19,20 . However, immunological differences among the substrains under conditions of obesity need to be further analyzed.…”
mentioning
confidence: 92%
“…O tumor de Ehrlich é considerado uma neoplasia transplantável que tem origem epitelial maligna, que corresponde ao adenocarcinoma mamário de camundongos fêmeas 41 , 42 . Caracteriza-se como um modelo que prolifera rapidamente possuindo células pleomórficas e anaplásicas as quais apresentam relação núcleo citoplasma, nucléolos múltiplos e proeminentes, além do núcleo com a cromatina frouxa 43 .…”
Section: Tumor Ascítico De Ehrlichunclassified